The Impact of Public Policy and Membership of the EU on Regional Policy in Estonia - Garri Raagmaa (European Regional Science Association (ERSA), 2006)
The primary aim of the paper is to provide an overview of the development and topical issues of the Estonian regional policy along with public policy. In order to implement a public policy, choices must be made based on values, which in their turn considerably influence the actual result. Public policy is usually described as a process of making choices from the determination of the situation to evaluation of the policy being implemented. This process has often an irrational character, which is caused by limited information available to decision-makers and limited time. My approach moves on from the statement of Ludek Sukora and his colleagues (Balchin et al 1999, 163) which says that in Eastern European countries, thus, hypothetically in Estonia as well, the former centralised planning economy replaced by relatively small local governments under the conditions of new legislation, where national plans do not work and consistent regional development policies do not exist, has brought about a situation of uncertainty, application of ad hoc methods instead of long-term comprehensive planning, and the use of earlier experience in administrative techniques. Following the above I present following hypotheses: H1) governmental normative documents on regional development change frequently and are often contradictory; H2) institutions responsible for the implementation of regional policy are unstable; H3) national and EU plans do not work and sectoral development plans are not compatible; H4) regional political initiatives depend on activities of different officials or ministers - human factor is critical; H5) no attempts are being made in municipalities to achieve awareness of conceptual basics of national and EU policies and their objectives, instead, different lobbying methods have been applied. In theoretical part, we look at the concept of regional policy and it's changes in Europe. The empirical part will give a description of the Estonian regional and administrative polices in time, primarily based on observations, on the content analysis of documents and the written media, and interviews carried out in 1990-2005.
Keywords: 330